The Social Criticism on the Anthology of Poetry Portrait of Development by WS Rendra - Lestari, Sri Indah; Alfiawati, Riska; Sudarmaji, Sudarmaji (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2018)
This study aims to describe social criticism in the poetry anthology